2020
DOI: 10.1038/s41467-020-16056-4
|View full text |Cite
|
Sign up to set email alerts
|

Precise control of the interlayer twist angle in large scale MoS2 homostructures

Abstract: Twist angle between adjacent layers of two-dimensional (2D) layered materials provides an exotic degree of freedom to enable various fascinating phenomena, which opens a research direction-twistronics. To realize the practical applications of twistronics, it is of the utmost importance to control the interlayer twist angle on large scales. In this work, we report the precise control of interlayer twist angle in centimeter-scale stacked multilayer MoS 2 homostructures via the combination of wafer-scale highly-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
194
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(212 citation statements)
references
References 44 publications
14
194
2
2
Order By: Relevance
“…3 (e), all the other areas except the two-layered regions are shown in white color. It should be noted that for twisted bilayers, the shear mode disappears when the twist angle is between 4—40 degrees 5 , 44 . In such a case, the twist angle range can be roughly estimated by the lack of shear mode and the frequency of breathing mode.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 (e), all the other areas except the two-layered regions are shown in white color. It should be noted that for twisted bilayers, the shear mode disappears when the twist angle is between 4—40 degrees 5 , 44 . In such a case, the twist angle range can be roughly estimated by the lack of shear mode and the frequency of breathing mode.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, bilayer graphene can be transformed into a gate-tunable superconductor or into an insulator by choosing the right twist angle between the layers 4 . It is also reported that in multilayered MoS 2 , the twist angle between the layers can change the indirect bandgap 5 . Another example is the presence of a stacking-dependent symmetry variation that leads to valley polarization, which can be utilized for valleytronics applications 6 .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, exploring unconventional states of matter requires identifying systems where electronic correlations, topology, and electronic dispersions can be realistically controlled. In this regard, twisted van der Waals materials [1][2][3][4][5][6][7][8] provide a powerful solid state platform to realize exotic quantum phenomena. The tunability of twisted van der Waals materials stems from the emergence of a band structure that can be controlled by the twist between different two-dimensional materials [9,10].…”
Section: Introductionmentioning
confidence: 99%